Answer:
- x² +3x -8x -24
- (x² +3x) +(-8x -24)
- x(x +3) -8(x +3)
- (x +3)(x -8)
Explanation:
This is trying to help you understand a method of factoring trinomials.
The first step is to look at the linear term (-5x) and the constant term (-24) and identify the coefficients and their signs: -5 and -24.
The next step is to identify factors of -24 (the constant) that have a sum equal to -5 (the linear term coefficient). We can look at the ways that -24 can be factored:
-24 = 1(-24) = 2(-12) = 3(-8) = 4(-6)
The sums of these factor pairs are 1-24=-23, 2-12=-10, 3-8=-5, 4-6=-2. Of course, the pair we're looking for is +3 and -8.
The next step from here is to rewrite the linear term using these factors. (-5x=3x-8x) This is the first step of the sequence shown in the figure:
x² +3x -8x -24
The next step is to group these terms in pairs:
(x² +3x) +(-8x -24)
And then, to factor each pair using the distributive property:
x(x +3) -8(x +3)
Finally, finish the factoring, again using the distributive property:
(x +3)(x -8)